The entrepreneur's search for capital - Bruno, Albert V.; Tyebjee, Tyzoon T. (Journal of Business Venturing, 1985)
The popular media have been inundated with stories of the spectacular success of start-up companies whose very existence, let alone their meteoric growth, would not have been possible without the infusion of venture capital. By comparison, there is a dearth of scientific research on the topic of venture capital. In this article we take a systematic look at entrepreneurs in search of risk capital. This inquiry is based upon five data bases including surveys of venture capitalists and entrepreneurs. We have tracked 193 ventures which were denied venture capital, surveyed 179 new high-technology companies in Northern California, and reviewed the Dun & Bradstreet credit reports of 145 new ventures in California in SIC codes related to the high tech sector with follow-up interviews of 86 of these 145 start-ups.